Reformasi hukum keluarga di dunia Muslim - Wahib, Ahmad Bunyan (IJTIHAD Jurnal Wacana Hukum Islam dan Kemanusiaan, 2014)
This article discusses about the history and the development of family law reform in Muslim countries.This work has taken a lot benefits from Andersonâs works on Islamic law in the Muslim world for bothdata and perspective. Islamic family law reform started from the second decade of twentieth century(1915) with the issuance of two Ottoman Caliph decrees on wife rights to ask religious court to divorcethem from their husband. This reform was followed by Sudan (starting from 1916), Egypt (1920),Jordan (1951), Syria (1953), Tunisia (1956/1959), Morocco (1958), Iraq (1959), Pakistan (1961) and Iran(1967). The reformation aims to administrate the members of community in the filed of social,economy, politics, and law. From the perspective of modernization, Islamic family law reform inMuslim countries has shown the process of modernization from above.